Body growth and blood metabolite concentrations in Boran and Boran x Friesian bulls grazed on natural pastures: Effect of dry season dietary supplementation - Tegegne, Azage; Mukasa-Mugerwa, E. (Ethiopian Society of Animal Production, 1995)
Twenty-seven Boran and 37 Boran x Friesian bulls, weaned at six months of age, were allocated to either receive supplementary diet (16 percent crude protein and 10.8 MJ/kg DM energy) during the dry season or to serve as unsupplemented controls until 21 months of age. Body weight measurements were taken monthly and two sets of blood samples were collected from all bulls during each of the two dry seasons and one intervening wet season during the 15-month study period. Plasma samples were used for determination of plasma total protein, albumin, globulin, blood urea nitrogen (BUN) and glucose concentrations. Over the study period, overall body weight gain was positive for all treatment groups, but was higher in supplemented than in control bulls and in Boran x Friesian than in Boran bulls. Within genotype, supplementary feeding increased overall body growth by 2.2- and 1.6-fold in Boran and Boran x Friesian bulls, respectively. Within genotype, supplemented bulls had higher total protein and albumin levels, while plasma globulin, BUN and glucose were not affected. On average, Boran bulls had lower concentrations of total protein and globulin, but higher albumin and BUN levels than the Boran x Friesian bulls. Blood glucose concentrations were not influenced by dietary supplementation, did not differ between genotypes and showed no consistent trends over time in the two genotypes. Body weight was positively correlated with plasma total protein (0.54) and globulin (0.49) concentrations, but negatively related with albumin/globulin ration (-0.48) and blood urea nitrogen (-0.57). It was concluded that the body growth of young bulls grazing natural pastures during the wet season was adequate and dry season dietary supplementation improved growth in both Boran and Boran x Friesian bulls. Determination of blood metabolites considered in this study did not assist in assessing the nutritional status of young Boran and Boran x Friesian bulls using the types of feeds and at the level of supplementation provided.